2017
DOI: 10.1103/physrevfluids.2.044601
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of tracer trajectories in rotating turbulent flows

Abstract: The geometry of passive tracer trajectories is studied in two different types of rotating turbulent flows; rotating Rayleigh-Bénard convection (RBC; experiments and direct numerical simulations) and rotating electromagnetically forced turbulence (EFT; experiments). This geometry is fully described by the curvature and torsion of trajectories and from these geometrical quantities we can subtract information on the typical flow structures at different rotation rates. Previous studies, focusing on non-rotating ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 39 publications
10
20
0
Order By: Relevance
“…Figure 3(a,b) shows the autocorrelation of the velocity in the xy and z directions at the cell centre, respectively. The time lag is nondimensionalised by the local Kolmogorov time scales, given in Table 1 calculated from direct numerical simulations using the same parameter settings, see Alards et al (2017) and Rajaei (2017) for the details of the numerical method. Note that the Kolmogorov time scale differs depending on the position within the cylinder.…”
Section: Lagrangian Velocity Autocorrelationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3(a,b) shows the autocorrelation of the velocity in the xy and z directions at the cell centre, respectively. The time lag is nondimensionalised by the local Kolmogorov time scales, given in Table 1 calculated from direct numerical simulations using the same parameter settings, see Alards et al (2017) and Rajaei (2017) for the details of the numerical method. Note that the Kolmogorov time scale differs depending on the position within the cylinder.…”
Section: Lagrangian Velocity Autocorrelationmentioning
confidence: 99%
“…Rossby (1969); Boubnov & Golitsyn (1986); Zhong et al (1993); Liu & Ecke (1997); Sakai (1997); Vorobieff & Ecke (2002); Kunnen et al (2008); King et al (2009); Zhong & Ahlers (2010); Niemela et al (2010); Kunnen et al (2010); Weiss & Ahlers (2011 a ); Kunnen et al (2014); Ecke & Niemela (2014); Rajaei et al (2017), numerical simulations, e.g. Julien et al (1996); Kunnen et al (2006); King et al (2009); Schmitz & Tilgner (2009); Stevens et al (2010); Julien et al (2012 b ); Stellmach et al (2014); Horn & Shishkina (2015); Alards et al (2017) and theoretical analysis, e.g. Chandrasekhar (1961); Chan (1974); Constantin et al (1999); Doering & Constantin (2001); Vitanov (2003); King et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies were primarily focused on the turbulent dispersion of Lagrangian particle pairs [5] and tetrads [6], the entropy production rates along individual Lagrangian trajectories [7] for convection volumes with aspect ratios Γ = L/H ≤ 4 where L is a horizontal extension (side length or diameter). Characteristic turnover times and the geometry of Lagrangian trajectories were analyzed numerically in closed non-rotating [8] and in rotating cells [9,10]. Laboratory experiments of turbulent convection pioneered the use of smart particles to measure local heat fluxes [11] along individual particle tracks.…”
Section: Introductionmentioning
confidence: 99%
“…Instantaneous measures for this geometry are the curvature and torsion of trajectories. Such curvature and torsion measurements of tracer trajectories in rotating RBC have shown that the predictions for the scaling of curvature and torsion probability density functions (PDFs) derived for homogeneous isotropic turbulence (HIT) [12][13][14][15] are recovered, as long as measurements are performed in the turbulent bulk [16]. In the BLs, the PDFs scale differently consistent with the type of BL, which is the Prandtl-Blasius type in the regime dominated by the LSC and the Ekman type in the regime affected by vertically aligned vortices.…”
Section: Introductionmentioning
confidence: 99%
“…In RBC, trajectories are additionally expected to be affected by the large-scale coherent flow structures at larger timescales. We therefore extend the previous study on instantaneous measurements of the geometry of tracer trajectories [16] to scale-dependent measurements of this geometry by computing the directional change of tracer trajectories in (rotating) RBC up to the timescale of the large-scale coherent flow structures.…”
Section: Introductionmentioning
confidence: 99%